Implementasi KRPPA Di Kota Madiun Sebagai Wujud Gendermainstream - Sari, Siska Diana; Arizal, Nizam Zakka; Eviningrum, Sulistya; Kharisma, Bintang Ulya; Perdana, Yudita Ayu Widya; Aa’nisaa, Rara (Fakultas Hukum, Universitas Boyolali, 2024)
Abstract This study examines the KRPPA or Women-Friendly and Child-Caring Village program in Madiun City to improve public understanding of gender equality. Legislation governing gender equality is contained in the 1945 Constitution Article 27 Paragraph (1) and Article 28 I Paragraph (2). This program exists as an effort to increase public awareness of gender equality between men and women and protection of children in Indonesia. KRPPA is expected to become a new epicenter for development based on the fulfillment of women's and children's rights. All aspects of development must be felt by residents of the Village without exception, in accordance with the Sustainable Development Goals (SDGs). The Ministry of Women's Empowerment and Child Protection (Kemen PPPA) together with the Ministry of Villages, Development of Disadvantaged Regions and Transmigration (Kemendesa) developed the Women-Friendly and Child-Caring Village (DRPPA) and Women-Friendly and Child-Caring Village (KRPPA) policies. KRPPA is a sub-district that integrates gender perspectives and children's rights in the governance of sub-district governance, sub-district development, and development and empowerment of sub-district communities, which are carried out in a planned, comprehensive, sustainable manner, in accordance with the vision of Indonesian development. The purpose of this study is to examine the Implementation of Women-Friendly and Child-Caring Sub-districts (KRPPA) in Pilot Project Sub-districts in Madiun City. The method used in this study: this study is an empirical juridical legal research with a socio-legal research approach. The research location is in several sub-districts that are used as KRPPA Pilot Parjects in Indonesia. Abstrak Penelitian ini mengkaji tentang progam KRPPA atau Kelurahan Ramah Perempuan dan Peduli Anak di Kota Madiun untuk dapat meningkatkan pemahaman masyarakat tentang kesetaraan gender. Peraturan perundangan yang mengatur tentang kesetaraan gender terdapat di UUD 1945 Pasal 27 Ayat (1) dan Pasal 28 I Ayat (2). Program ini ada, sebagai upaya peningkatan kesadaran masyarakat tentang kesetaraan gender antara laki-laki dan perempuan serta perlindungan terhadap anak di Indonesia. KRPPA diharapkan dapat menjadi episentrum baru bagi pembangunan yang berbasis pemenuhan hak perempuan dan anak. Semua aspek pembangunan harus dirasakan manfaatnya oleh warga Kelurahan tanpa terkecuali, sesuai dengan tujuan Pembangunan Berkelanjutan (SDGs). Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (Kemen PPPA) bersama kementerian Desa Pembangunan Daerah Tertinggal dan Transmigrasi (Kemendesa) mengembangkan kebijakan Desa Ramah Perempuan dan Peduli Anak (DRPPA) dan Kelurahan Ramah Perempuan dan Peduli Anak (KRPPA). KRPPA merupakan kelurahan yang mengintegrasikan perspektif gender dan hak anak dalam tata kelola penyelenggaraan pemerintahan kelurahan, Pembangunan kelurahan, serta pembinaan dan pemberdayaan masyarakat kelurahan, yang dilakukan secara terencana, menyeluruh, berkelanjutan, sesuai dengan visi pembangunan Indonesia. Tujuan penelitian ini untuk mengkaji Implementasi Kelurahan Ramah Perempuan Dan Peduli Anak (KRPPA) Di Kelurahan Pilot Project Di Kota Madiun. Metode yang digunakan dalam penelitian ini : penelitian ini merupakan penelitian hukum yuridis empiris dengan pendekatan socio-legal research. Lokasi penelitian di beberapa kelurahan yang dijadikan Pilot parject KRPPA di Indonesia